Do Hybrid Legal Systems Matter in Foreign Legal-Aid Programmes? Some Philosophical Aspects of Legal Aid in Uzbekistan as Provided by the Donor States. Issue 2 (4th June 2021) - Ismatov, Aziz
Abstract: Since the fall of socialism in Eastern Europe, the former Soviet Union, and some states of Southeast Asia, the international financial institutions and individual donor states have initiated wide-scale legal-aid programmes to assist these states in their transition from socialism to a market economy. Whereas the aid from financial institutions vis-à-vis recipient states is often agreed upon specific conditionalities, the donor states design their foreign legal aid according to individual preferences, although sometimes with references to universal goals. Currently, various donor states provide legal aid to Uzbekistan. Given the fact that Uzbekistan is the former Soviet Republic that still bears multiple traces of a socialist legal system and additionally integrates indigenous informal law, this research provides an analysis of how different donor states base their legal-aid activities on entirely different philosophies and levels of gravity, and how receptive the hybrid structure of Uzbekistan's law is towards such aid.